2006
DOI: 10.1063/1.2225418
|View full text |Cite
|
Sign up to set email alerts
|

Periodic solution and chaotic strange attractor for shunting inhibitory cellular neural networks with impulses

Abstract: By using the continuation theorem of coincidence degree theory and constructing suitable Lyapunov functions, we study the existence, uniqueness, and global exponential stability of periodic solution for shunting inhibitory cellular neural networks with impulses, dx(ij)dt=-a(ij)x(ij)- summation operator(C(kl)inN(r)(i,j))C(ij) (kl)f(ij)[x(kl)(t)]x(ij)+L(ij)(t), t>0,t not equal t(k); Deltax(ij)(t(k))=x(ij)(t(k) (+))-x(ij)(t(k) (-))=I(k)[x(ij)(t(k))], k=1,2,...] . Furthermore, the numerical simulation shows that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The Hopfield neural networks with impulse effect are studied, where the criteria on the existence, uniqueness and global stability of periodic solution are obtained. Further, Gui chaos strange attractor was also found [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The Hopfield neural networks with impulse effect are studied, where the criteria on the existence, uniqueness and global stability of periodic solution are obtained. Further, Gui chaos strange attractor was also found [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 81%
“…As is known to all that (1) can exhibit chaotic phenomenons [6][7][8][9][10] . In order to show it clearly, we give the following example.…”
Section: Preliminaries and Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new type of system has been introduced: dynamic systems with impulses, which are neither purely continuous time nor purely discrete time and exhibit a combination of continuous time and discrete time characteristics. Furthermore, the concept of chaos and strange attractors is very attractive for ecologists now (see [6,7]). For example, Gui [6,7] found that some systems are capable of exhibiting strange attractors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the concept of chaos and strange attractors is very attractive for ecologists now (see [6,7]). For example, Gui [6,7] found that some systems are capable of exhibiting strange attractors. In the present paper, we not only proved the existence and global exponential stability of periodic solutions for the model, but also found a new strange attractor which is caused by impulsive perturbations.…”
Section: Introductionmentioning
confidence: 99%